Physical and sealing properties of BaO–Al2O3–SiO2–CaO–V2O5 glasses for solid oxide fuel cell applications. (26th February 2022) - Wang, Sea-Fue; Hsu, Yung-Fu; Liao, Yi-Le; Yang, Yuan-Jie; Jasinski, Piotr
Abstract: In this study, the properties of BaO–Al2 O3 –SiO2 (SAB) glasses incorporated with CaO and V2 O5 as the network modifier and additive, respectively, are evaluated. The electrical resistivities of the glasses decrease upon the addition of CaO but increase upon increasing their V2 O5 content because the V 5+ species lower the ionic mobility of the glasses. The addition of V2 O5 improves the wettability of the glasses on the Crofer 22 APU substrate, and thus, increases the fracture strength at the glass–Crofer 22 APU couple. Among the glasses evaluated, the SAB glass with a CaO content of 20 wt% and V2 O5 content of 2 wt% (SAB-Ca20V2) present excellent sealing properties because it adheres well to both the Zr0·92 Y0·08 O2-δ (YSZ) and Crofer 22 APU substrates; no pores, cracks, or interfacial phases are present at the interfaces, confirming the good chemical and thermal compatibility of the glass–substrate pairs at high temperatures. After SAB-Ca20V2 is sealed on the Crofer 22 APU substrate at 850 °C, the leakage rate of the glass is low (<0.015 sccm⋅cm −1 at 800 °C for 200 h), indicating negligible deterioration of its sealing efficiency and revealing its remarkable potential for use in solid oxide fuel cell applications. Highlights: BaO–Al2 O3 –SiO2 glasses added with CaO and V2 O5 were studied for SOFC applications. Electrical resistivity declined with CaO addition, but escalated with V2 O5 content. V2 O5 addition increased the fracture strength at the glass–Crofer 22 APU interface. Excess CaO and V2 O5 ruined sealing/mechanical properties as bonded to Crofer22APU. SAB-Ca20V2 glass showed trivial degradation at 800 °C displays its great potential for use in SOFCs.